2018
DOI: 10.1590/s1677-5538.ibju.2016.0581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes with or without renorrhaphy during open partial nephrectomy: A propensity score-matched analysis

Abstract: Purpose:Renorrhaphy in partial nephrectomy may damage intraparenchymal vessels and compress the renal parenchyma, which may lead to the formation of renal artery pseudoaneurysms or vascularized parenchymal volume reduction. Using propensity score matching, we compared surgical outcomes following non-renorrhaphy and renorrhaphy techniques for open partial nephrectomy (OPN) for T1a renal tumors.Materials and Methods:We retrospectively analyzed data from 159 patients with normal contralateral kidneys who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Tachibana et al found that the risk of pseudoaneurysm was lower with SLT than with DLT during open partial nephrectomy. 18 Similarly, in patients undergoing RAPN for cT1a disease, the risk of pseudoaneurysm was lower when SLT with soft coagulation was used. [4][5][6][7] Early unclamping may help prevent pseudoaneurysm after partial nephrectomy because Kondo et al reported that early unclamping allowed surgeons to identify arterial bleeding from the resection bed before suturing the renal parenchyma and control it by adding an internal suture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tachibana et al found that the risk of pseudoaneurysm was lower with SLT than with DLT during open partial nephrectomy. 18 Similarly, in patients undergoing RAPN for cT1a disease, the risk of pseudoaneurysm was lower when SLT with soft coagulation was used. [4][5][6][7] Early unclamping may help prevent pseudoaneurysm after partial nephrectomy because Kondo et al reported that early unclamping allowed surgeons to identify arterial bleeding from the resection bed before suturing the renal parenchyma and control it by adding an internal suture.…”
Section: Discussionmentioning
confidence: 98%
“…Tachibana et al. found that the risk of pseudoaneurysm was lower with SLT than with DLT during open partial nephrectomy 18 . Similarly, in patients undergoing RAPN for cT1a disease, the risk of pseudoaneurysm was lower when SLT with soft coagulation was used 4–7 .…”
Section: Discussionmentioning
confidence: 99%
“…The soft coagulation system of the VIO 300D was used with the effect level set at 7 and output of 80 W, using a ball-type electrode to increase the contact area with the resection bed. Tachibana et al also showed that the non-renorrhaphy (inner layer sutures only) technique using the soft-coagulation system may produce a lower risk of RAP than renorrhaphy (inner and outer layer sutures) (19). Similarly, for RAPN in patients with cT1a renal tumors, RAP did not occur with hemostasis by soft coagulation only, namely with inner sutures and without outer sutures (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we are now largely reducing the contrast material and radiation exposure dose by using a full iterative reconstruction method, a forward-projected model-based iterative reconstruction solution (FIRST; Canon Medical Systems, Otawara, Japan), while improving the visualization of the peripheral renal arteries (Morita et al 2020 ). Furthermore, the frequency of RAP in our institution has recently decreased due to improvements in surgical techniques, such as early unclamping, avoidance of deep excision into the renal sinus, and the non-renorrhaphy technique (Omae et al 2015 ; Tachibana et al 2018 ; Kondo et al 2015 ). However, the management of RAPs after partial nephrectomy should be carefully considered, especially in non-high-volume centers, because they can lead to life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%